2020
DOI: 10.3389/fmolb.2020.616575
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Carbon Dots to Combat COVID-19

Abstract: Viral diseases are considered as a global burden. The eradication of viral diseases is always a challenging task in medical research due to the high infectivity and mutation capability of the virus. The ongoing COVID-19 pandemic is still not under control even after several months of the first reported case and global spread. Neither a specific drug nor a vaccine is available for public use yet. In the pursuit of a promising strategy, carbon dots could be considered as potential nanostructure against this vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 88 publications
0
36
0
Order By: Relevance
“…the amino-terminal or S1 subunit is involved in the RBD, whereas the carboxy-terminal or S2 subunit is responsible for the formation of the stalk, and thereby, assists in virus fusion. In general, the S protein recognizes the host angiotensin-converting enzyme (ACE) receptor, and leads to membrane fusion and cellular entry (Kotta et al, 2020b), while E protein mediates the virion assembly and their release, and M protein describes the envelope shape (Alanagreh et al, 2020;Malik, 2020). On the other hand, N proteins are associated with the RNA genome packaging during viral replication to form the complete virions (Alanagreh et al, 2020).…”
Section: Genomic Organization Of Sars-cov-2 and Host Immune Responsesmentioning
confidence: 99%
“…the amino-terminal or S1 subunit is involved in the RBD, whereas the carboxy-terminal or S2 subunit is responsible for the formation of the stalk, and thereby, assists in virus fusion. In general, the S protein recognizes the host angiotensin-converting enzyme (ACE) receptor, and leads to membrane fusion and cellular entry (Kotta et al, 2020b), while E protein mediates the virion assembly and their release, and M protein describes the envelope shape (Alanagreh et al, 2020;Malik, 2020). On the other hand, N proteins are associated with the RNA genome packaging during viral replication to form the complete virions (Alanagreh et al, 2020).…”
Section: Genomic Organization Of Sars-cov-2 and Host Immune Responsesmentioning
confidence: 99%
“…It was concluded that the biosensor demonstrated high sensitivity and selectivity toward the target virus and presented potential application in rapid sensing of very infectious diseases. Interestingly, there are few reports of the potential use of carbon dots in antiviral therapy and also for biosensing purposes, including biosensing of HIV DNA sequences [138,139]. A FRET-based DNA biosensor using single-stranded DNA (ss-DNA) functionalized CQDs as the energy donor and gold nanoparticles (AuNPs), AuNPs/graphene oxide (GO), as efficient quenchers demonstrated the efficiency down to the femtomolar level for the detection of HIV DNA (Figure 6).…”
Section: Photoluminescent Sensing Of Moleculesmentioning
confidence: 99%
“…It is well known that early, rapid, low-cost, and accurate diagnosis of SARS-CoV-2 is of great importance in order to prevent further spreading of the virus. Although there have not yet been any studies reported of using pristine or modified CQDs as a viral therapy to combat or for the detection of COVID-19, the above-reported examples are undoubtedly showing that carbon dots have a great potential for theranostic application against SARS-CoV-2 [138]. Moreover, CQDs have also found many applications in food safety regarding the detection of different nutrients, toxins, and restricted substances or foodborne pathogenic bacteria.…”
Section: Photoluminescent Sensing Of Moleculesmentioning
confidence: 99%
“…Carbon-based nanomaterials, such as surface-functionalized graphene oxides, carbon nanotubes, and carbon dots, have shown their effectiveness against various types of viral infections, including enterovirus, influenza virus, human immunodeficiency virus, and human alphaherpesvirus [ 12 , 13 , 14 , 15 , 16 , 17 ]. Notably, the highly biocompatible carbon dots, developed using different precursors (e.g., organic salt, amino acids, polymers) or different methods (e.g., hydrothermal, microwave, electrochemistry, or pyrolysis), act as disparate inhibitors at different stages of viral infection, including virus attachment, penetration, replication, and budding [ 18 , 19 , 20 , 21 , 22 , 23 ]. Most reported carbon dots have been demonstrated to interact with the viral surface protein and inhibit their penetration into host cells [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most reported carbon dots have been demonstrated to interact with the viral surface protein and inhibit their penetration into host cells [ 18 , 19 , 20 ]. On the other hand, the inhibition of viral replication by carbon dots is accomplished by the alteration of enzymes that are essential for viral genome replication and finally for budding [ 12 , 21 , 22 , 23 ]. However, most studies overlook the role of polymeric structures on the surface of carbon dots in their interaction with the virus; thus, we were motivated to reveal the flexible polymeric carbon nanomaterials underpinning the action of these dots in the treatment of viral infections.…”
Section: Introductionmentioning
confidence: 99%